The benefits of cooperative learning: an overview - Trung, Dang Ngoc; Truong, Do Xuan (Technium Education and Humanities, 2023)
In the current trend, the trend of international cooperation, global integration, equipping students with skills such as: critical thinking, communication, cooperation, social awareness, creative thinking is an urgent problem. This requires an alternative teaching approach to promote active learning among students of which “cooperative learning” is one method that can meet this requirement. To better understand the benefits of cooperative learning, We performed a review of 84 published papers related to cooperative learning worldwide. Research results show the benefits of cooperative learning in motivating students, improving learning outcomes and developing skills for students. In addition, we also noticed a number of barriers affecting the organization of cooperative learning. These research results play an important role to build an active teaching strategy and also serve as a reference base for further research.